Penanaman Nilai Pendidikan Karakter Islami pada Anak Jalanan - Yazidul Busthomi; Maskuri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The purpose of this study is to describe, analyze, and interpret the instillation of Islamic character education values ​​among street children at the Raudlatul Ulum 1 Islamic Boarding School in Ganjaran, Gondanglegi, Malang. This study uses a qualitative approach, a type of research that produces findings that are not obtained by statistical procedures or other quantification tools. This can lead to research on a person's life, history, behavior, or interactional relationships. This concept emphasizes that qualitative research is characterized by an emphasis on the use of non-statistical (mathematical) methods, especially in the data analysis process, to produce research findings naturally. The researcher determined the appropriate data collection techniques, namely: 1. Interview techniques; 2. Participant observation techniques; 3. Documentation methods. The instillation of Islamic character education values ​​among street children at the Raudlatul Ulum 1 Islamic Boarding School in Ganjaran, Gondanglegi, Malang, includes: 1) Establishing study groups at the Raudlatul Ulum 1 Islamic Boarding School as a strategy for instilling Islamic character education; 2) Implementation of Islamic character education values ​​in daily life at Raudlatul Ulum 1 Islamic Boarding School; 3) Evaluation and monitoring of the program to instill Islamic character education values ​​in street children at Raudlatul Ulum 1 Islamic Boarding School are critical aspects in ensuring the success and sustainability of this initiative.